Pengabdian Masyarakat di Tiban Indah 2 Dengan Pembuatan Rajutan Benang Dan Plastik - Dian Dermawan; Olivia Rebeca Tamaris Gultom; Shane Edwin; Lisa Lisa; Hayllen Stathany; Gusti Irawan; Jupri Arianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Knitting is making cloth, clothing or fashion equipment from knitting yarn with two needles, knitting activities can also be used as high-value and attractive goods in the eyes of foreign tourists. This knitting not only produces items such as clothes but can also produce items for accessories such as key chains that can be shaped according to taste, knitting can be done by hand or machine. Basic techniques in knitting are the upper and lower stitches, the knitted material is not only obtained from yarn but can also be obtained from used plastic that can be recycled and is also environmentally friendly. The purpose of this study is to introduce to local residents that knitting activities that can provide income or income for the business and also provide experiences that can be shared with many people. The location of the place of knitting is in the area of ​​Tiban Indah 2 coinciding in the Sun Beach Housing Rt 002 / Rw 010. In this knitting activity also often involves the mothers around the housing by dividing their respective tasks.